Penggunaan Disinfektan Spray Minyak Atsiri Kulit Kayu Manis sebagai Penurunan Angka Kuman Meja Makan - Husniya Tazkiya Azzahra; Sri Haryanti; Choirul Amri; Yamtana Yamtana (Jurnal Kesehatan Lingkungan Mandiri, 2026)
Dining table hygiene in restaurants is a critical issue because microbial contamination can lead to foodborne illness. Natural disinfectants made from cinnamon bark essential oil (Cinnamomum burmannii) offer a safer alternative due to their antibacterial compounds, particularly cinnamaldehyde and eugenol. This study aimed to evaluate the effectiveness of cinnamon bark essential oil spray at concentrations of 2%, 4%, and 6% in reducing the germ count on dining tables. A quasi-experimental method with a Non-Equivalent Pretest–Posttest Control Group Design was employed. The study involved 24 dining table germ count measurements with six replications for each treatment and control group. Data were analyzed using Paired Samples t-Test, One-Way ANOVA, and LSD tests. The results showed that the average germ count decreased from 104 to 30.8 CFU/cm² at 2% concentration, from 101.2 to 23.2 CFU/cm² at 4%, and from 99 to 13.3 CFU/cm² at 6%. Statistical analysis indicated significant reductions before and after treatment (p = 0.000) and significant differences among concentrations (p = 0.009). Therefore, cinnamon bark essential oil has strong potential as a natural disinfectant for restaurant dining tables.